2020
DOI: 10.3390/ijms21176408
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenon of Clopidogrel High On-Treatment Platelet Reactivity in Ischemic Stroke Subjects: A Comprehensive Review

Abstract: Clopidogrel is increasingly being used for the secondary prevention of ischemic stroke according to the updated guidelines on acute stroke management. Failure to achieve a drug response is referred to as clopidogrel resistance. Similarly, a higher activation of platelets during clopidogrel therapy—high on-treatment platelet reactivity—is equivalent to a reduced effectiveness of a therapy. Clopidogrel resistance is considered to be a common and multifactorial phenomenon that significantly limits the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…To date, association studies between genetic variants, cardiovascular events, HPR and LPR have focused on polymorphisms on PON1 (p.Q192R), ABCB1 (C.3435C>T) polymorphisms, and particularly the CYP2C19 gene [ 12 , 13 , 14 , 15 ]. CYP2C19, an enzyme of the cytochrome P450 (CYP450) superfamily, is considered the key enzyme related to the bioactivation of clopidogrel through the two-step oxidative process that leads to the formation of 2-oxo-clopidogrel and the active metabolite clopi-H4 [ 16 , 17 ]. Only some genetic variants of CYP2C19 have been widely explored and their relation to the therapeutic response to clopidogrel has been established.…”
Section: Introductionmentioning
confidence: 99%
“…To date, association studies between genetic variants, cardiovascular events, HPR and LPR have focused on polymorphisms on PON1 (p.Q192R), ABCB1 (C.3435C>T) polymorphisms, and particularly the CYP2C19 gene [ 12 , 13 , 14 , 15 ]. CYP2C19, an enzyme of the cytochrome P450 (CYP450) superfamily, is considered the key enzyme related to the bioactivation of clopidogrel through the two-step oxidative process that leads to the formation of 2-oxo-clopidogrel and the active metabolite clopi-H4 [ 16 , 17 ]. Only some genetic variants of CYP2C19 have been widely explored and their relation to the therapeutic response to clopidogrel has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Hypercoagulability still remains the baseline background of a higher risk of cerebrovascular events, incluing ischemic stroke [ 3 , 4 ]. Many studies have shown that high platelet reactivity, higher levels of fibrinogen or hyperactivated properties of the coagulation system may correspond to the increased incidence of recurrent vascular events [ 5 , 6 ]. Therefore, TEG ® is widely applicated in the evaluation of clot transformation and monitoring the coagulation properties of blood in different branches of medicine [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical significance of a similar phenomenon in relation to clopidogrel is also increasingly being raised. Considering that the mechanisms and background of the low responsiveness to clopidogrel are similar to those of aspirin, analogous and comparable clinical consequences should also be expected [ 12 ]. Other authors investigated the impact of clopidogrel resistance on the clinical course of stroke and reported that it is associated with worse clinical conditions and poor early and late prognosis [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%